PENERAPAN STRATEGI BELAJAR PQ4R (PREVIEW, QUESTION, READ, REFLECT, RETICE, REVIEW) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VA SD NEGERI 35 PETANI - Irnawati, Irnawati; Syahrilfuddin, Syahrilfuddin; Hamizi, Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the lack of IPS student learning outcomes can be seen from the results of the students' social studies class VA SD Negeri 35 Petani with an average value of 60.65. Therefore, the researchers provide an alternative implementation strategies in the classroom to learn PQ4R VA SD Negeri 35 Petani in the academic year 2014/2015. This research aims to improve learning outcomes IPS VA grade students of SD Negeri 35 Petani with learning PQ4R Implementation Strategy. Form of research is the Classroom Action Research (PTK) with 2 cycles. Based on research data anlisis after applying the learning strategies PQ4R, the average percentage of the activity of teachers in the first cycle 74.99% increased to 91.06% in the second cycle. The average percentage of student activity also increased, namely 67.85% in the first cycle increased to 82.14% in the second cycle. Student learning outcomes in basic score by the average value of 60.65 and the first cycle increased with an average value of 75.00 class with a 23.66% increase in the percentage of learning outcomes and the percentage of students who completed 84.61%, and the second cycle increased again by an average of 82.30 with the percentage improvement class learning outcomes 35.69% and the percentage of students who completed 88.46%. These results indicate that the application of learning strategies to improve learning outcomes PQ4R IPS VA grade students of SD Negeri 35 Petani.Key Words: Learning Strategies PQ4R, IPS Learning Outcomes